Islamic Values Based Classroom Management in Improving Student Discipline and Learning Motivation - Rachmatulloh Rusli; Abdulmuhyi (Jurnal Pengabdian Cita Masyarakat, 2026)
Moral degradation and low discipline alongside poor learning motivation within Islamic religious education at boarding schools strongly necessitate highly effective classroom management strategy innovations. This community service initiative aims to implement Islamic values based classroom management at Miftahul Khoer Two Boarding School to systematically overcome these specific problems. The research utilizes a Participatory Action Research design featuring systematic stages including diagnostic observation, interactive workshops, simulations, implementation mentoring, and comprehensive evaluation. The intervention outcomes reveal a highly significant systemic improvement; teacher managerial competence increased by thirty five percent, student discipline rose by twenty five points, and learning motivation surged by twenty seven points. Program success was ultimately achieved through establishing participatory classroom agreements, applying humanistic approaches, and balancing educational rewards with punishments. In conclusion, integrating Islamic spiritual values with modern management principles proves exceptionally effective in transforming authoritarian teaching approaches into genuine empowerment, fostering internal discipline, and strengthening student learning commitments.